2000
DOI: 10.2307/253925
|View full text |Cite
|
Sign up to set email alerts
|

A Basis for Modelling the Costs of Supplier Selection: The Economic Tender Quantity

Abstract: In this paper, we consider the decision a purchaser must make regarding the number of suppliers that should be invited to submit a tender for a certain purchase. On the one hand, the costs of sending invitations to tender, the costs of evaluating the tenders received, and the costs of communicating the outcome to the suppliers that were not selected, all increase with the number of suppliers that are invited to tender. On the other hand, with every additional tender, the purchaser might obtain a better bid. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…In this paper we propose an alternative approach which differs in a number of ways from the existing formal analyses by Barua et al (1997), De Boer et al (2000) and Berger et al (2004). In fact, our approach includes three heuristics, all based on the same principles but varying slightly in terms of the precision of input information required from the purchaser.…”
Section: Presentation and Discussion Of Relevant Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In this paper we propose an alternative approach which differs in a number of ways from the existing formal analyses by Barua et al (1997), De Boer et al (2000) and Berger et al (2004). In fact, our approach includes three heuristics, all based on the same principles but varying slightly in terms of the precision of input information required from the purchaser.…”
Section: Presentation and Discussion Of Relevant Literaturementioning
confidence: 99%
“…Still, while extremely simple and easy to communicate and enforce, these heuristics are – as explained earlier on in this paper – based on very crude simplifications of reality. The ETQ model developed in De Boer et al (2000) already addressed this and showed that only using the expected value of the contract as the basis for deciding how many suppliers should be invited to bid, may lead to poor decisions if one considers each case of supplier selection separately. After all, if the relative differences between suppliers’ bids are negligible, asking for more bids will hardly help.…”
Section: Discussionmentioning
confidence: 99%
“…For invited bidding, the question arises of how many suppliers should actually be invited to submit a bid. This question has already been investigated in a quantitative way (De Boer, Van Dijkhuizen & Telgen, 2000;Lansdowne, 1996). Inviting more suppliers will increase the costs of the whole evaluation process as more hours need to be spent on the tenders (tendering or evaluation costs).…”
Section: Criteria For Choosing Award Procedures From Literaturementioning
confidence: 99%
“…For a certain number of bids the total costs (adding up the best expected bid and tendering costs) are optimal (see Figure 7). This optimal number of suppliers is defined as the Economic Tender Quantity (ETQ) (De Boer et al, 2000). In the De Boer et al article, a mathematical model is presented for calculating this ETQ along with the minimum expected total costs.…”
Section: Criteria For Choosing Award Procedures From Literaturementioning
confidence: 99%
“…Peleg et al (2002) study a setting where the buyer chooses how many suppliers to recruit for an auction, but they do not study the possibility that the buyer runs a test auction to update her information about existing suppliers, which is the focus of our paper. de Boer et al (2000) find the "Economic Tender Quantity" when there are costs associated with sending RFQs, evaluating suppliers' tenders, and communicating the results of the competition. In our model, we study the same type of cost, but incorporate incumbent suppliers and allow multiple auctions.…”
mentioning
confidence: 99%